Enhanced Recovery After Surgery (ERAS) for Benign Minimally Invasive Gynecology [3D]. (May 2018) - Suh, Christina; Wörndle, Natalie; Mollner, Magdalena; Balica, Adrian
Abstract : INTRODUCTION: Enhanced recovery after surgery (ERAS) protocols use evidence based strategies to optimize postoperative recovery. In colorectal surgery, ERAS has been shown to decrease length of stay and narcotic use without increasing complications or readmissions. These principles are now being applied to gynecologic surgery as well. Our objective was to identify literature published regarding ERAS protocols in benign minimally invasive gynecology. METHODS: Publications identified using the PubMed database, written in English and published between January 2012 and September 2017, were included for analysis. Searches were conducted using the terms "enhanced recovery after surgery" or "enhanced recovery" in combination with one of the following: gynecologic surgery, benign gynecologic surgery, minimally invasive gynecologic surgery. RESULTS: We identified 33 relevant publications, including 9 retrospective cohort studies, 3 randomized controlled trials, 2 case control studies, and 1 prospective cohort study. Review articles, including 2 ERAS society recommendations, were excluded from analysis. Four publications assessed benign pathology only, whereas 5 publications included benign and malignant pathology. Of the 3 publications assessing benign minimally invasive gynecology, 2 assessed vaginal hysterectomies only, as opposed to laparoscopic or robotic procedures. Common interventions included preoperative counseling, nausea prophylaxis, multimodal analgesia, early ambulation, and early feeding. Common outcomes measured included length of stay and readmission rate. CONCLUSION: There is limited data evaluating the efficacy of ERAS protocols for gynecologic surgery, and there is nearly no published data for benign minimally invasive gynecology. Given the increasing numbers of minimally invasive procedures, more studies are needed to assess the potential benefits of ERAS in this field.